Clinical Benefits of Olaparib in Mexican Ovarian Cancer Patients With Founder Mutation BRCA1-Del ex9-12 - Gallardo-Rincón, Dolores; Montes-Servín, Edgar; Alamilla-García, Gabriela; Montes-Servín, Elizabeth; Bahena-González, Antonio; Cetina-Pérez, Lucely; Morales Vásquez, Flavia; Cano-Blanco, Claudia; Coronel-Martínez, Jaime; González-Ibarra, Ernesto; Espinosa-Romero, Raquel; María Alvarez-Gómez, Rosa; et al. (Frontiers in Genetics, 2022)
Background. Ovarian Cancer (OC) is gynecologic cancer with the highest mortality rate. It is estimated that 13 to 17% of ovarian cancers are due to heritable mutations in BRCA1 and BRCA2. The BRCA1 (BRCA1-Del ex9-12) Mexican founder mutation is responsible for 28 to 35% of the cases of ovarian cancer. The aim was to describe the PFS of OC patients treated with olaparib, emphasizing patients carrying the Mexican founder mutation (BRCA1-Del ex9-12). Methods. In this observational study, from 107 patients with BRCAm, 35 patients were treated with olaparib from November 2016 to May 2021 at the Ovarian Cancer Program (COE) of Mexico; patient information was extracted from electronic medical records. Results. Of 311 patients, 107 (34.4%) were BRCAm; 71.9% (77/107) were BRCA1 from these 27.3% (21/77) was BRCA1-Del ex9-12, and 28.1% (30/107) were BRCA2 mutations. Only 35 patients received the Olaparib treatment, the median follow-up was 12.87 months. The PFS of BRCA1-Del ex9-12 was NR (Non-Reach), however, 73% of the patients received the treatment at 36 months vs. 11.59 months (95% CI 10.43-12.75) in patients with other BRCAm (P=0.008). Almost 50% of patients required dose reduction due to toxicity; the most frequent adverse events were hematological in 76.5% and gastrointestinal in 4%. Conclusion. Mexican OC BRCA1-Del ex9-12 patients treated with olaparib had a significant increase in PFS regardless of the line of treatment compared to other mutations in BRCA.